Plato's Cratylus : argument, form, and structure - Riley, Michael W. (Value inquiry book series, 2005)
This book explains how the Cratylus, Plato's apparently meandering and comical dialogue on the correctness of names, makes serious philosophical progress by its notorious etymological digressions. While still a wild ride through a Heraclitean flood of etymologies which threatens to swamp language altogether, the Cratylus emerges as an astonishingly organized evaluation of the power of words.